This Time They Are Different : Heterogeneity and Nonlinearity in the Relationship Between Debt and Growth - Eberhardt, Markus; Presbitero, Andrea (Washington, D.C. : International Monetary Fund, 2013)
We study the long-run relationship between public debt and growth in a large panel of countries. Our analysis takes particular note of theoretical arguments and data considerations in modeling the debt-growth relationship as heterogeneous across countries. We investigate the issue of nonlinearities (debt thresholds) in both the cross-country and within-country dimensions, employing novel methods and diagnostics from the time-series literature adapted for use in the panel. We find some support for a nonlinear relationship between debt and long-run growth across countries, but no evidence for common debt thresholds within countries over time.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet